2010
DOI: 10.1055/s-0030-1255330
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy for Head and Neck Cancer

Abstract: Treatment for patients with head and neck cancer requires a multidisciplinary approach. Radiotherapy is employed as a primary treatment or as an adjuvant to surgery. Each specific subsite dictates the appropriate radiotherapy techniques, fields, dose, and fractionation scheme. Quality of life is also an important issue in the management of head and neck cancer. The radiation-related complications have a tremendous impact on the quality of life. Modern radiotherapy techniques, such as intensity-modulated radiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(69 citation statements)
references
References 42 publications
1
67
0
1
Order By: Relevance
“…Radiation therapy is frequently employed in the management of HNC . Optimal radiation doses depend on the tumour type, site and disease stage . Radiosensitive tumours such as lymphomas require relatively low doses of 30–36 Gy .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Radiation therapy is frequently employed in the management of HNC . Optimal radiation doses depend on the tumour type, site and disease stage . Radiosensitive tumours such as lymphomas require relatively low doses of 30–36 Gy .…”
Section: Introductionmentioning
confidence: 99%
“…Radiosensitive tumours such as lymphomas require relatively low doses of 30–36 Gy . Carcinomas are not as radiosensitive . In general, primary tumours and gross lymphadenopathy require a total dose of 70 Gy or more .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Radiation oncology in the head and neck has evolved considerably over recent years with the advent of intensity-modulated XRT (IMRT) and volumetric arc therapy (VMAT), now favored over traditional threeand two-dimensional techniques, which are able to offer precise radiation delivery, while minimizing the dose to surrounding normal structures without compromise of target coverage. 37 Furthermore, image-guided planning and specific patient immobilization and positioning techniques with the use of a thermoplastic mask are able to expose the larynx and minimize dose delivery to surrounding tissues, while creating a reproducible set-up for the whole duration of XRT treatment. These new techniques avoid exposure to salivary glands, upper aerodigestive mucosa, and pharyngeal constrictors and several studies have reported reduced radiation-related side effects and improved functional and quality-of-life outcomes.…”
Section: Intensity-modulated Radiation Therapymentioning
confidence: 99%